Excessive copper induces lignin biosynthesis in the leaves and roots of two citrus species: Physiological, metabolomic and anatomical aspects - Xin Zhou; Xing Xiong; Fei Lu; Wenqing Shi; Yu Zhou; Ningwei Lai; Li-Song Chen; Zeng-Rong Huang (Ecotoxicology and Environmental Safety)
Excessive copper (Cu) of rhizosphere inhibited the growth and development of citrus seedlings. Lignin deposition on the cell wall promotes plant Cu tolerance. However, the lignin biosynthesis in citrus leaves and roots that respond to Cu toxicity is not fully understood. In this study, young seedlings of ‘Xuegan’ [Citrus sinensis (L.) Osbeck, a less Cu-tolerant species] and ‘Shatian pomelo’ [Citrus grandis (L.) Osbeck, a more Cu-tolerant species] were treated with nutrient solution containing 0.5 (as Control), 100, 300 or 500 µM Cu for 15 weeks in sandy culture. By the end of treatments, citrus leaves and roots were sampled to investigate the biomass allocation, Cu distribution, the lignin biosynthesis and deposition. The results indicated that Cu stress from 100 to 500 µM increased the root/shoot biomass ratio, promoting Cu and lignin accumulation in the leaves and roots of the tested citrus species. Besides, 300 µM Cu stress increased the accumulation of three lignin monomers of citrus species. The metabolomic profile indicated that Cu toxicity altered the lignin components of citrus species. The citrus roots are more prominent in the lignin precursor biosynthesis under Cu toxicity than citrus leaves. The histochemical staining supported that Cu stress improved the deposition of both guaiacy and syringy lignin units in citrus roots. The enzyme activity and gene expression revealed that activating lignin-biosynthetic enzymes, such as L-phenylalanine ammonia-lyase, peroxidase and laccase, played an essential role in lignin biosynthesis. Our results demonstrated that excessive Cu induced lignin biosynthesis in citrus leaves and roots to different extents. The findings from the present study increased our understanding of lignin biosynthesis in Cu-stressed citrus species, which would provide a theoretical basis for the citrus Cu-tolerant mechanisms.